"It's just something engrained in them": examining organizational citizenship behaviors within part-time campus recreation center employees. Issue 3 (4th May 2017) - Scola, Zach; Schaeperkoetter, Claire C.; Lower, Leeann M.; Bass, Jordan R.
ABSTRACT: Sport scholars have sparsely examined the contributions of part-time employees in the workforce. This study contributes to the gap in the literature by exploring a recreation center's part-time student staff participation in organizational citizenship behaviors (OCBs). These behaviors can simply be described as "going above and beyond job requirements" and have been suggested to increase organizational effectiveness [Podsakoff, P. M., & MacKenzie, S. B. (1997). Impact of organizational citizenship behavior on organizational performance: A review and suggestion for future research. Human Performance, 10 (2), 133–151]. Furthermore, the authors sought to understand how these OCBs contributed to organizational effectiveness. Data were collected through semi-structured interviews of student employees. The findings from this study showed that multiple OCBs were apparent at this recreation center, and the students felt that these behaviors positively impacted the organization's effectiveness. This case study extends the lines of research on part-time employees and OCBs in sport.